以不正方法取得營業秘密之未遂犯 ──美國法著手犯的借鏡 Criminal Attempt of Improperly Acquiring Trade Secrets Under the Trade Secret Act ―A Lesson from the Concept of “Attempt” Under the United States Criminal Law - 陳秉訓 Ping-Hsun Chen (交大法學評論)
本文意在參酌美國聯邦《經濟間諜法》（Economic Espionage Act, EEA）與《模範刑法法典》（Model Penal Code, MPC）第5.01條之著手犯之法制，來思考我國營業秘密法犯罪行為中的未遂犯意涵。本文指出意圖竊取他人營業秘密、並進而著手以不正方法取得他人之資訊者，只要該行為人以為到其所取得的資訊為營業秘密，其即應負未遂犯之責。該認識之成立可基於被害單位客觀上有執行營業秘密合理保密措施。 This article provides the definition of criminal attempt of stealing trade secrets under the Trade Secret Act through studying the United States’ Economic Espionage Act and criminal attempt under Model Penal Code § 5.01. This article argues that a person shall be held criminally liable for his attempt to acquire other’s trade secret by an unjust measure, as long as he knew the stolen information was a trade secret. Such knowledge may be inferred from circumstances showing that the owner has implemented reasonable measures to protect its trade secrets.